Cellular Alteration of the Oral Mucosa due to Orthodontic Appliances and Tobacco Smoking: A Cytomorphometric Study - Marla, Vinay; Baral, Dharanidhar; Pokharel, Prabhat Ranjan; Shrestha, Ashish; Gyawali, Rajesh; Giri, Jamal (Journal of College of Medical Sciences-Nepal, 2019)
Introduction: Fixed orthodontic treatment causes chronic low grade irritation on the oral mucosa. Tobacco smoking is considered to be a risk factor in the development of oral cancer. This study involves a cytomorphometric analysis on the buccal mucosal cells in patients undergoing fixed orthodontic treatment who are tobacco smokers. Methods: Exfoliated buccal mucosal cells were obtained from orthodontic patients (smokers & non-smokers) as well as smokers and non-smokers who are not undergoing any orthodontic treatment. Smears were stained with rapid PAP stain and digital images of 50 cells were analysed using the Image J software. Results: Statistical analysis revealed that there were significant increase in the values of nuclear and cell diameter between non-smokers undergoing orthodontic treatment and smokers (p<0.001 & p=0.014 respectively), and between non-smokers undergoing orthodontic treatment and smokers undergoing orthodontic treatment (p<0.001 & p=0.015 respectively). Also, nuclear area and cell area showed significant differences between many of the study groups. Conclusion: It can be concluded that there are nuclear and cellular alterations in patients undergoing fixed orthodontic treatment who are smokers